Pengembangan Supervisi Refleksi â€œGibbsâ€ untuk Peningkatan Kepatuhan Kebersihan Tangan Petugas Kesehatan - Muhammad Fandizal; Hanny Handiyani (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2020)
Supervision is an actuating part of the management function to achieve the goals of the organization. Supervision of hand hygiene compliance 94 health workers conducted by infection, prevention, & control link nurse (IPCLN) using direct supervision methods. The purpose of developing indirect supervision is because direct supervision is not effective to be carried out, so the development of supervision reflection "Gibbs Reflective Cycle" to assess the compliance of nurses in doing hand hygiene. The method used is the Pilot Study involving internal and external reform agents. Sample selection using purposive sampling as many as 30 respondents consisting of nurses, doctors, and caregivers. The implementation of the study concluded that the compliance of officers in performing hand hygiene was 72.33%, and then Fish Bone analysis was conducted to determine the main problem. The problem was solved by developing the organization using the Kurt Lewin method and using plan, do, check and action (PDCA). The program is carried out by making manuals and operational procedures standard (OPS) for the supervision of reflection. The recommendation given is to propose a draft reflection supervision manual and the OPS that has been prepared should be endorsed by the President Director and disseminating information to the Nursing Manager, the head of the room, and / IPCLN.